SCIENTIFIC AND METHODOLOGICAL BASIS OF ENDURANCE FORMATION IN YOUNG ATHLETES AGED 10-16 - Rakhmatova, Dilnoza (Журнал иностранных языков и лингвистики, 2022)
This article is devoted to the formation of the quality of endurance in young athletes, the distribution of training loads by intensity zones, the influence of aerobic, aerobic-anaerobic, mixed and anaerobic loads on the body of those involved, five components characterizing training loads when performing physical exercises, as well as the use of the following methods in the development of general endurance: method of continuous exercise with measured load, method of repeated and interval exercise, game method, competitive method and method of round-robin training.